Functional Properties of Natural Human PAX6 and PAX6(5a) Mutants - Chauhan, Bharesh K. (2004)
PURPOSE: Pax6 is essential for development of the eye, brain, and pancreas. Two major products of PAX6 are specific DNA-binding proteins, PAX6 and PAX6(5a). PAX6(5a) contains a short insertion influencing its DNA-binding activity. Heterozygous mutations in PAX6 result in abnormal eye development implicating haploinsufficiency. Deletions of one PAX6 allele result in aniridia characterized by severe ocular phenotypes. Approximately 10% of PAX6 mutations encode missense mutations. These mutations usually cause less severe abnormalities than does aniridia. The moderate phenotypes raise the possibility that different ocular tissues are differently sensitive to specific mutations. To test this hypothesis, we probed functional properties of individual mutated Pax6 proteins in a variety of conditions. METHODS: Mutations in PAX6 and PAX6(5a) were introduced by site-directed mutagenesis and tested by transfections in four cell lines using reporters containing three different Pax6 binding sites. Pax6 binding to DNA was studied by electrophoretic mobility shift assays. RESULTS: Functional studies of PAX6 and PAX6(5a) and their eight natural missense (G18W, R26G, A33P, S43P, G64V, I87R, V126D and R128C) and two nonsense (R317X and S353X) disease-causing mutants revealed unexpected pleiotropic effects in gene regulation, not predicted by the PAX6-DNA crystal structure. Transactivation by PAX6 and PAX6(5a) was dependent on the location of mutation, type of DNA-binding site, and cellular environment. CONCLUSIONS: This work provides evidence that activation by PAX6 and PAX6(5a) is modulated by specific cellular environments. It is likely that moderate phenotypes associated with PAX6 missense mutations originate from abnormal protein function in a restricted number of ocular cell types.